Distinct Patterns of University Students Study Crafting and the Relationships to Exhaustion, Well-Being, and Engagement - Mülder, Lina Marie; Schimek, Sonja; Werner, Antonia Maria; Reichel, Jennifer L.; Heller, Sebastian; Tibubos, Ana Nanette; Schäfer, Markus; Dietz, Pavel; Letzel, Stephan; Beutel, Manfred E.; Stark, Birgit; Simon, Perikles; et al. (Frontiers in Psychology, 2022)
Job crafting has been established as a bottom-up work design instrument for promoting health and well-being in the workplace. In recent years, the concepts of job crafting have been applied to the university student context, proving to be positively related to student well-being. Building on person-centered analyses from the employment context, we assessed approach study crafting strategy combinations and the relationships to students’ exhaustion, study engagement, and general well-being. Data from 2,882 German university students were examined, collected online during the summer term in 2020. Using latent profile analysis, we found five distinct crafting groups, which showed discriminate validity with regard to emotional exhaustion, engagement, and well-being. The results underscore the positive role of study crafting for students’ health and well-being. They further indicate a less important role of increasing social resources for emotional exhaustion when combined with a moderate increase in structural resources and a moderate increase in challenging demands. Our findings imply that interventions to promote study crafting should be considered to promote student health and well-being.